JAUS to EtherCAT Bridge: Toward Real-Time and Deterministic Joint Architecture for Unmanned Systems - Jie Sheng; Sam Chung; Leo Hansel; Don McLane; Joel Morrah; Seung-Ho Baeg; Sangdeok Park (Journal of Control Science and Engineering)
The Joint Architecture for Unmanned Systems (JAUS) is a communication standard that allows for interoperability between Unmanned Vehicles (UVs). Current research indicates that JAUS-compliant systems do not meet real-time performance guidelines necessary for internal systems in UVs. However, there is a lack of quantitative data illustrating the performance shortcomings of JAUS or clear explanations on what causes these performance issues or comparisons with existing internal communication systems. In this research, we first develop a basic C++ implementation of JAUS and evaluate its performance with quantitative data and compare the results with published performance data of Controller Area Network (CAN) to determine the feasibility of the JAUS standard. Our results indicate that the main reason of JAUS’s poor performance lies in the latency inherent in the hierarchical structure of JAUS and the overhead of User Datagram Protocol (UDP) messages, which has been used with JAUS and is slower than the high-speed CAN. Additionally, UDP has no scheduling mechanism, which makes it virtually impossible to guarantee messages meeting their deadlines. Considering the slow and nondeterministic JAUS communication from subsystems to components, which is JAUS Level 3 compliance, we then propose a solution by bringing Ethernet for Control Automation Technology (EtherCAT) to add speed, deterministic feature, and security. The JAUS-EtherCAT mapping, which we called a JEBridge, is implemented into nodes and components. Both quantitative and qualitative results are provided to show that JEBridge and JAUS Level 3 compliance can bring not only interoperability but also reasonable performance to UVs.